Wave motion in elastic solids - Graff, Karl F. (Dover Publications, 1991)
Comprehensive, self-contained coverage of a variety of topics ranges from the elementary theory of waves and vibrations in strings to three-dimensional theory of waves in thick plates. Emphasis on analytical and experimental results, in addition to theoretical development. Appendices contain introductory material on elasticity, transforms, experimental techniques. Over 100 problems.